Gender discrimination in the business school’s C-suite? Evidence from aggregate decomposition approaches - Caudill, Steven B.; Mixon, Franklin G.; Faria, João Ricardo; Santoyo, Julissa Y. (Frontiers in Education, 2022)
Workplace discrimination continues to at least be perceived as a problem by faculty and staff in higher education. The current study extends the academic literature in this area by exploring the possibility of gender discrimination in the wages of academic deans. Using data on deans’ salaries from more than 200 colleges and schools of business in the U.S., we focus our analysis on aggregate decompositions from both the usual Oaxaca-Blinder decomposition approach and the more powerful inverse probability weighting technique. Aggregate decomposition results from both the usual Oaxaca-Blinder decomposition approach and inverse probability weighting fail to support the existence of gender discrimination in administrative wages in academia. They do, however, support new theoretical research asserting that the publicness of academic administrators’ salaries works to circumvent any wage discrimination based on gender or race.